Unraveling the Trauma of the Protagonist in ’My Dark Vanessa’ Novel (2020) - Weni Kristina Nainggolan (Morphosis: Journal of Literature, 2024)
The study is entitled “Traumatic Experiences of Main Character in My Dark Vanessa Novel (2020)”. The purpose of this study is to analyze the traumatic experiences by main character when she was teenager and deal with the traumatic in the novel “My Dark Vanessa”. The method of this research is qualitative method. The data sources uses in this study were from the dialogue, sentences taken from the novel “My Dark Vanessa”. The researcher uses the Concept trauma by Catchy Carruth (1996). The result showed that trauma experienced by the main character has several symptoms experienced main character such as intrusion or re-experiencing, nightmares, mood changes or cognitive, flashbacks and avoidance. The results of this analysis indicate that Vanessa suffered from trauma caused by the tragic events she experienced when she was teenager due to adult. The researcher also found how to deal with traumatic such as secret identity, compartmentalizing, denial, safe place to tell the truth, silencing, and the last right brains therapy. Keywords: abused, deal, literature, main character, traumatic